Linking the economics of water, energy, and food: A nexus modeling approach - Al-Riffai, Perrihan; Breisinger, Clemens; Mondal, Md. Hossain Alam; Ringler, Claudia; Wiebelt, Manfred; Zhu, Tingju (International Food Policy Research Institute, 2017)
We use an innovative methodology to model the socioeconomic linkages between water, energy, and food in the East Nile Basin. Based upon a theoretical nexus framework, the methodology is expanded into a quantifiable modeling suite that under-lies the analysis of each of three country case studies. The advantages are that, despite resource shortages being a challenge, the modeling suite aids in devising policies and strategies that formulate these sectoral interdependencies and provide the evidence-based research results necessary for their design in a way that exploits synergies existing across sectors, countries, and regions (Al-Zubari n.d.). This paper lays out the methodology and gives an example of an application and scenarios by focusing on three countries in the East Nile Basin. This methodology paper will be followed by three individual country case studies that highlight the water, energy, and food nexus for each.